SPECTROPHOTOMETRIC METHOD FOR THE DETERMINATION OF AMIKACIN IN PURE AND PHARMACEUTICAL DOSAGE FORM - G., Surya Teja; M., Gurupadayya B.; K., Venkata Sairam (International Journal of Current Pharmaceutical Research, 2018)
Objective: The aim of the study was to develop an easy, sensible and rapid method for the estimation of amikacin in both pure and marketed formulation using the spectrophotometric method. Methods: Due to lack of chromophoric group in the amikacin, it was derivatized with 0.1 mmol chloranillic acid reagent. For the estimation of amikacin, Shimadzu UV-1700 model spectrophotometer with UV probe software was used. The method was based on simple charge transfer complexation of the drug with a p-chloranillic acid reagent to give a purple coloured product which was measured at 524nm against blank solution. Results: The derivatised product of amikacin was detected at a wavelength of 524 nm. Linearity was observed with the concentration range of 20-100 Âµg/ml with a regression coefficient of 0.9803. Results of all the parameters were within the acceptance criteria with % RSD less than 2. Conclusion: The spectroscopic method was validated as per ICH guidelines and was found to be applicable for routine quantitative analysis of amikacin in marketed formulations also. The results of linearity, precision, accuracy LOD and LOQ were within the specified limits. The method is highly sensitive, robust, reproducible and specific. Â 